Bacteriophage removal efficiency of in-line coagulation with ceramic membrane filtration - Ladawan Wattanachira (2018)
© 2017, Chulalongkorn University 1. All rights reserved. The main objectives of this study are to evaluate the removal efficiency of bacteriophage Qβ using in-line coagulation with ceramic membrane filtration at different coagulant dosages, ceramic membrane pore sizes and initial bacteriophage Qβ concentrations. Raw water was collected from the Ping River, Chiang Mai, Thailand, and spiked with bacteriophage Qβ to prepare an initial concentration of 8x106 PFU/ml. According to the resulted, it was found that the smaller pore sizes membrane yield higher bacteriophage Qβ log removal. However, the use of a ceramic membrane alone could not remove bacteriophage Qβ completely. In-line coagulation combined with ceramic membrane filtration was conducted. The optimal polyaluminum chloride (PACl) doses for the 1.0, 0.5 and 0.1 μm pore size membranes were 2.5, 2.0 and 1.5 mg-Al/L, respectively. Bacteriophage Qβ removal at the optimal PACl dose was more than 6.7 log in all cases. The results of effect of different initial bacteriophage Qβ concentration on the removal efficiency showed that in-line coagulation with ceramic membrane at all pore sizes can completely remove bacteriophage Qβ when the initial concentration was low (5x105 PFU/ml). However, the higher initial bacteriophage Qβ concentrations (4x106 and 8x107 PFU/ml) required a higher PACl dose to obtain effective bacteriophage Qβ removal.